The Effect of Outward and Inward Internationalisation on Different Types of Innovation : Evidence from UK SMEs - Idris, Bochra; Saridakis, George; Khan, Zaheer (Elsevier, 2021)
This paper empirically examines the effect of outward internationalisation, inward internationalisation activities and outward-inward internationalisation (i.e., exporting and importing) on different types of innovation undertaken by UK SMEs. Specifically, we differentiate between product innovation and process innovation and examine the potential effect that they can generate individually and in combination. The results show that both inward and outward internationalisation support product and process innovation in SMEs. However, such an effect is found to be stronger for the combined outward-inward internationalisation operations than for the single mode undertaken by SMEs. The results are found to be robust across the different types of innovation. However, sub-sample analysis shows that, although innovation responds to different internationalisation operations in micro and small firms, for medium-sized firms, only the combination of outward and inward internationalisation operations increases the probability of undertaking both innovations. Using the organisational learning theory, we argue that engaging in both internationalisation activities simultaneously enables firms to acquire a more diverse and richer set of knowledge and key information — through double loop learning, which is translated into increased levels of innovation. Hence, our results have important theoretical, managerial, and policy implications and stimulate the existing debate in the area.
Keywords: SMEs; Outward internationalisation; Inward internationalisation; Learning; Innovation; Product innovation; Process innovation; small and medium-sized enterprises; fi=Kansainvälinen liiketoiminta|en=International Business|